If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying c + (-8 + 6c) = 0 Remove parenthesis around (-8 + 6c) c + -8 + 6c = 0 Reorder the terms: -8 + c + 6c = 0 Combine like terms: c + 6c = 7c -8 + 7c = 0 Solving -8 + 7c = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 7c = 0 + 8 Combine like terms: -8 + 8 = 0 0 + 7c = 0 + 8 7c = 0 + 8 Combine like terms: 0 + 8 = 8 7c = 8 Divide each side by '7'. c = 1.142857143 Simplifying c = 1.142857143
| 16(4y-5)=8(7y+5) | | 5x-7/3=xx | | 5x-7u/2=2u-; | | -2(x-3)(x+3)-18=0 | | 3(5w-2)-4(3w-5)=w | | 28-x+30-x+3x+x=40 | | -7+6.5(1+2.5s)=-16.5 | | (T+0.5)4=5 | | -6xy+6xy= | | X(2)=5(5) | | f(-2)=(4m-3)/(m-7) | | 2(x-5)=7-2x | | 3sinx-4cosx-2=0 | | .2(7-x)=4 | | 5-3x-(-4x+6)=-(8x+11)-(3x-10) | | 42.5/y=x | | 2=(3+x)+3(2) | | x^(-1/5)=(1/3) | | x^-1/5=1/3 | | 8x+41y+10=180 | | 2n/3=4 | | x-x+3x+x+30+28=40 | | 5h-7-3h=2(h-14) | | a^3-64= | | (2c+1)=(c-5) | | 4x^2+4y^2-16x+32y-20=0 | | (2c-1)=(c-5) | | 12y-18/2 | | 16x-3=68+13+4x | | 2x+4x+2x+1+5x-6=60 | | r/s=25 | | 9x+1=9(1)+2 |